Perception of Online Lectures among Undergraduate Medical, Dental and Nursing Students during COVID-19 Pandemic: a Cross-Sectional Study at a Tertiary Teaching Hospital - Sarraf, Deependra Prasad; Rauniar, Gajendra Prasad; Karn, Basant Kumar; Kushwaha, Ramayan Prasad; Keshwar, Shashi (Birat Journal of Health Sciences, 2021)
Introduction: The COVID-19 pandemic significantly affected medical education and has forced educators to switch to online teaching-learning activities worldwide. Online teaching-learning activities has ensured the safe delivery of the lectures to the students. Objective: To assess the perception of students towards online lectures and to analyze the perceived barriers to online learning in our context during the COVID-19 lockdown period. Methodology: A cross-sectional online descriptive study was conducted among undergraduate students at a tertiary teaching college in Eastern Nepal during September-November 2020. The link of the Google form consisting of the semi-structured questionnaire was sent to the students through email. Descriptive statistics frequency and percentage were calculated using Microsoft Excel 2010. The study was approved by the Institutional Review Committee (IRC/2069/20). Results: A total of 211 students participated in the study. Mean age of the students was 20.5±1.5 years. Out of 211, 130 (61.61%) students used smartphones to attend online lectures and 176 (83.41%) students had not attended any online classes before the COVID-19 pandemic. The most common perceived advantage of the online lectures was availability of recorded lectures (186, 88.15%) whereas reduced interaction (179, 84.83%) was the most common disadvantage. More than half (126, 59.72%) of the students disagreed/strongly disagreed that online lectures are more effective than traditional face-to-face lectures. Conclusions: Most of the students had negative perception towards the online lectures. The study findings recommend using a hybrid of conventional face-to-face classroom based teaching and newer online teaching-learning activities for delivering medical education.